Risk factors, causative organisms and sensitivity patterns of infective keratitis in a tertiary care hospital in Rawalpindi - Amna Rizwan; Asfandyar Asghar; Syed Ali Hasan Naqvi; Ume Sughra; Hassan Raza (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the risk factors, causative organisms, sensitivity patterns and treatment outcomes of infective corneal ulcers. Methods: The is a prospective cohort study carried out from January 2018 to December 2019 at the Department of Ophthalmology, Fauji Foundation Hospital (FFH) Rawalpindi. A total of 65 eyes of 65 patients of corneal ulcer meeting the inclusion criteria were evaluated and corneal scrapes were sent for microbiological assessment. Variables studied were age, gender, risk factors, onset and duration of symptoms, best corrected visual acuity (BCVA), treatment and complications. Results: Out of 65 eyes of 65 patients, 40 (61.5%) were females and 25 (38.4%) were males. Most common local risk factor was ocular surgery (29.2%) followed by ocular trauma (23.1%). Diabetes was present in 44.6% of the cases. Culture results after corneal scrapings were positive for 39 (60%) of the total samples, while 26 (40%) had no growth. Bacterial growth was present in 51.3% of eyes, fungal in 28.2% while 20.5% of the eyes were infected with polymicrobial organisms. Most common pathogens were Pseudomonas (25.6%) that were most sensitive to ciprofloxacin. By the end of the follow-up period 40 cases (61.5%) showed improvement. Conclusion: This study concluded that isolated Pseudomonas was the most common pathogen. Prompt diagnosis with culture sensitivity tests are very much needed in developing countries to avoid blindness due to keratitis. Keywords: Infective keratitis, risk factors, corneal ulcer, culture sensitivity.